Efeitos da associação da aflatoxina B1 com aspartame em parâmetros bioquímicos e comportamentais em ratos - Souto, Naieli Schiefelbein (2020)
Mycotoxins are substances produced by fungi, natural contaminants of various foods. Aflatoxins are mycotoxins produced mainly by fungi of the Aspergillus genus, with aflatoxin B1 (AFB1) being the most frequent and the most toxic. AFB1 has carcinogenic, mutagenic and teratogenic effects, is converted in the liver to 8,9-epoxide, a metabolite that reacts with cellular macromolecules, including proteins, RNA and DNA. In this way, AFB1 alters hematological parameters and promotes an imbalance in the oxidative system, especially in antioxidant enzymes. Sweeteners are substances used as substitutes for sucrose, among them aspartame (ASP), which is widely used in food formulations and in the pharmaceutical industry. The toxicity mechanism of ASP is mainly based on the induction of oxidative stress and can act on different tissues. Considering the presence of both AFB1 and ASP in a meal, as well as their mechanisms of toxicity, they can promote the development of oxidative stress, imbalance in enzyme defenses and facilitate the development of behavioral changes. In this study, we investigated the exposure to AFB1 (250 μg / kg, ig) and / or ASP (75mg / kg, ig) in the animals' behavior through the Open Field, Marble Burying test, Nesting test and Splash test, and biochemical parameters after 7 and 14 days. The results showed changes in behavioral parameters, evidenced by the increase in time spent in the center in the open field test, increase in the number of balls buried and decrease in the time of cleaning the face in the sucrose spray test in the animals treated with AFB1 + ASP after 7 and 14 days. There was a change in oxidative stress markers, represented by a decrease in the activity of the enzyme catalase (CAT) in the liver and kidney after 7 days of exposure and an increase in activity after 14 days in all groups. Glutathione-S-transferase (GST) increased in the liver and kidney after 7 and 14 days, the ascorbic acid content decreased in the liver, cortex and hippocampus only in the longest treatment. Likewise, non-protein thiols (NPSH) and antioxidant power using reduced iron (FRAP) decreased in the liver, kidney, cortex and hippocampus only after 14 days of exposure. The lipid peroxidation determined by thiobarbituric acid reactive substances (TBARS) increased in the 7-day treatment only in the hippocampus, and after 14 days of exposure to AFB1 + ASP there was an increase in this marker in the liver, kidney, cortex and hippocampus. We observed a reduction in SOD-2 immunoreactivity in the hippocampus after treatment with AFB1 or ASP. It can be concluded that the administration of AFB1 and ASP alter oxidative parameters in the liver, kidney, cerebral cortex and hippocampus, both isolated and associated, in addition to promoting changes in the parameters related to depression and anxiety analyzed in the open field, Marble Burying test and Splash test . Thus, we emphasize the importance of knowing the toxic effects and the synergism that can occur between these food components, which may be able to promote an imbalance and thus affect and/or facilitate the development of diseases.